The role of perceived security and social influence on the usage behavior of digital banking services: An extension of the technology acceptance model - Quynh, NgoHai; Truong, LeMinh (Edelweiss Applied Science and Technology, 2023)
The goal of this research is to identify the variables influencing individual commercial bank customers’ intentions to use digital banking services. Digital banking is a relatively emerging research context that helps to complement and clarify marketing structures more clearly when combined with different factors to reflect convenience, usefulness, and distinct digital experiences for customers, thereby enhancing brand value for banks. Collecting data from 400 customers of banks in Vietnam is done through an online survey to ensure safety during the epidemic season. Data are analyzed according to the procedure from Cronbach’s Alpha test, EFA to CFA, and tested by the SEM model. The results show that the perceived security factor has the most substantial influence on customers’ behavioral intentions, thereby driving their actual behavior. Additionally, the usefulness, simplicity, and social influence of behavioral intentions for digital banking services all stimulate customer behavior. In the digital environment, this study suggests that following social phenomena and ensuring customer information security and transactions are extremely important. The results lead to shaping a culture-technology acceptance model based on TAM. That provides important insights and implications for the theoretical underpinnings of security perception, social influence, and usage behavior, such as how they are formed, roles, and relationships interrelationships between them in the digital environment.